Prevalence of dementia in Latin America: a collaborative study of population-based cohorts - Nitrini, Ricardo; Bottino, Cassio M. C.; Albala, Cecilia; Custodio Capunay, Nilton Santos; Ketzoian, Carlos; Llibre Rodriguez, Juan J.; Maestre, Gladys E.; Ramos-Cerqueira, Ana Teresa A. [UNESP]; Caramelli, Paulo (Cambridge University Press, 2009)
Background: Dementia is becoming a major public health problem in Latin America (LA), yet epidemiological information on dementia remains scarce in this region. This study analyzes data from epidemiological studies on the prevalence of dementia in LA and compares the prevalence of dementia and its causes across countries in LA and attempts to clarify differences from those of developed regions of the world.Methods: A database search for population studies on rates of dementia in LA was performed. Abstracts were also included in the search. Authors of the publications were invited to participate in this collaborative study by sharing missing or more recent data analysis with the group.Results: Eight studies from six countries were included. The global prevalence of dementia in the elderly (>= 65 years) was 7.1% (95% CI: 6.8-7.4), mirroring the rates of developed countries. However, prevalence in relatively young subjects (65-69 years) was higher in LA studies The rate of illiteracy among the elderly was 9.3% and the prevalence of dementia in illiterates was two times higher than in literates. Alzheimer's disease was the most common cause of dementia.Conclusions: Compared with studies from developed countries, the global prevalence of dementia in LA proved similar, although a higher prevalence of dementia in relatively young subjects was evidenced, which may be related to the association between low educational level and lower cognitive reserve, causing earlier emergence of clinical signs of dementia in the LA elderly population.
Keywords: aging; epidemiology; Alzheimer's disease; vascular dementia; developing countries; education; illiteracy